2008
DOI: 10.1152/ajpheart.00622.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonselective endothelin-1 receptor antagonism on cardiac mast cell-mediated ventricular remodeling in rats

Abstract: Murray DB, Gardner JD, Brower GL, Janicki JS. Effects of nonselective endothelin-1 receptor antagonism on cardiac mast cellmediated ventricular remodeling in rats. Am J Physiol Heart Circ Physiol 294: H1251-H1257, 2008. First published January 4, 2008 doi:10.1152/ajpheart.00622.2007.-The objective of this study was to investigate the effect a nonselective endothelin-1 (ET-1) receptor antagonist (bosentan) had on the acute myocardial remodeling process including left ventricular (LV) mast cells and matrix meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 45 publications
(63 reference statements)
4
48
0
Order By: Relevance
“…Initially investigated for potent vasoactive properties, evidence for ET-1 involvement in extracellular matrix turnover in disease states has been mounting (1,2,21,38,46). Clinical trials using ET A receptor antagonist in congestive heart failure patients reported lower systemic vascular resistance that resulted in higher cardiac index (6,31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initially investigated for potent vasoactive properties, evidence for ET-1 involvement in extracellular matrix turnover in disease states has been mounting (1,2,21,38,46). Clinical trials using ET A receptor antagonist in congestive heart failure patients reported lower systemic vascular resistance that resulted in higher cardiac index (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…An infrarenal AV fistula was created in rats as described previously (38,39). Briefly, a ventral abdominal laparotomy was performed to expose the aorta and caudal vena cava.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…lin receptor antagonist (25). Deschamps et al (26) showed that the increase in MMP-1 levels in porcine hearts associated with ischemia and reperfusion injury did not occur if the animals were treated with the ET-1-receptor A antagonist BQ-123.…”
Section: O V E M B E R -D E C E M B E R 2 0 1 0 C O N T R O L O F P Rmentioning
confidence: 99%